Malecón Tarapacá - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Se observo el Malecon Tarapaca con vista al rio y las edificaciones del ex Hotel Palace y ex Hotel del Turista.
ENGLISH: The Malecon Tarapaca overlooking the river and the buildings of the former Palace Hotel and former Hotel del Turista.

SPANISH: Se observo el Malecon Tarapaca con vista al rio y las edificaciones del ex Hotel Palace y ex Hotel del Turista.
ENGLISH: The Malecon Tarapaca overlooking the river and the buildings of the former Palace Hotel and former Hotel del Turista.
Malecon Tarapaca
Keywords: Iquitos (Perú)|~|Iquitos (Perú)|~|Malecon|~|Boulevard|~|Iquitos (Perú)|~|Iquitos (Perú)|~|Malecon|~|Boulevard|~|Iquitos (Perú)|~|Iquitos (Peru)|~|Malecon|~|Boulevard|~|Iquitos (Peru)